Practical aspects of meteorology and oceanography for mariners: A guide for the perplexed. Issue 1 (1st January 2018) - Aroucha, L. C.; Duarte, H. O.; Droguett, E. L.; Veleda, D. R. A.
Abstract: This paper aims to review and summarize the practical aspects of meteorology and oceanography for navigation, highlighting their influence on shiphandling. It is a review for: gathering, in a summarized way, some useful information for mariners, oceanographers, coastal managers, maritime students and maritime engineers; raising important topics for discussion about the theme; and identifying shortcomings that need more research. Aspects of navigation in Brazilian waters, specifically METÁREA V, are introduced as an example, bringing to light, when applicable, the practical aspects for shallow and restricted waters navigation. The parameters analysed were: clouds, rain, smog, fog, breeze, winds, waves, tides, and coastal and tidal currents. The passage of cold fronts can change winds direction. Also, local winds can overlap the effects of breezes, depending on its intensity. Dense fog, that can reduce visibility to less than 100 m, and rain, which according to its intensity, can reduce visibility to less than 500 m, are examples of some parameters that were checked and are able to reduce visibility when navigating. In addition, were reviewed the concepts of occurrence of rain and squall, and of frontal systems and the expected changes in local weather, pressure and air temperature with their approach. The importance of waves, tides and currents is also verified, especially for shallow and restricted waters navigation. Finally, the authors conclude that the analyses and comprehension of theses parameters are crucial for an efficient and safe navigation, and suggest shortcomings that need more research.